Bioreclamation of Sugar Mill Effluent Polluted Soil Using Earthworm and its Responses on Greengram (Vigna radiata L.) - P. Sundaramoorthy, P. Unnikannan, L. Baskaran*, AL.A. Chidambaram, (Journal of Phytology, 2009)
Reclamation is an emerging technology that uses to clean up pollutants (metals and organics) from the contaminated soil. In this field of reclamation the utilization of earthworm is a new approach, to remove the metals from the polluted soil. The present work has been carried out for the reclamation of sugar mill effluent contaminated soil with earthworm. The physico-chemical analysis of sugar mill effluent and the polluted soils revealed that they are toxic in nature because they contain higher amount of micronutrients and macronutrients, organic and inorganic chemicals and heavy metals. The presence of pollutants in the soil mainly affected the plant metabolism which leads to growth and yield reduction. In order to enrich the soil quality, earthworm was cultured upto 60 days in polluted soil.Ã‚Â After that, the various soil properties were analysed and good percentage of pollutant reduction was observed. Germination studies were conducted in bioreclamated soil and best germination was noticed under bioreclamated soil when compare with polluted soil.Ã‚Â Ã‚Â